AKIBAT HUKUM PERBEDAAN PENULISAN KETERANGAN ZAT YANG TERKANDUNG DI DALAM PRODUK AIR MINUM KEMASAN SMS DENGAN PRODUK YANG DIJUAL OLEH PT. AGRIMITRA UTAMA PERSADA PRODUSEN AIR MINUMAN KEMASAN SMS - Isnal Hevi; Zulfikar Jayakusuma; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Consumer protection is an integral part of sound business activities. In ahealthy business activity there is a balance of legal protection between consumersand producers. The absence of balanced protection leaves consumers in a weakposition. Moreover, if the product produced by the producer is a limited type ofproduct, the producer can abuse his monopolistic position.This type of research can be classified in the type of normative legalresearch, which discloses laws and regulations relating to legal theories that arethe object of research. The approach taken is using a qualitative analysisapproach by searching for data in books, journals and other scientific worksrelated to this research. The data sources used are primary and secondary legalmaterials.The conclusions that can be obtained from the results of the study areFirst, the legal consequences of differences in the writing of information onsubstances contained in SMS bottled water products with products sold by PT.Agrimitra Utama Persada, a producer of SMS bottled water, has an impact onconsumer health due to dishonesty by business actors and is contrary to Article 4Numbers 1 and 3, Article 8 Paragraph 1 letters d and f of Law Number 8 of 1999concerning Consumer Protection. Second, the responsibility of PT. AgrimitraUtama Persada against consumers who are harmed due to differences in thewriting of substance descriptions in the sms drink labels are fully responsible forthese claims. If the label attached to the packaging of the product being tradeddoes not match the truth or is misleading, it can be subject to sanctions as statedin the Consumer Protection Law Article 62 paragraph (1).Keywords: Consumer Protection, Bottled Water, Consumer Rights, LegalConsequences, Liability.